Signatures of the superfluid to Mott-insulator transition in the excitation spectrum of ultracold atoms - Clark, SR; Jaksch, D (2006)
We present a detailed analysis of the dynamical response of ultra-cold bosonic atoms in a one-dimensional optical lattice subjected to a periodic modulation of the lattice depth. Following the experimental realization by Stoferle et al [Phys. Rev. Lett. 92, 130403 (2004)] we study the excitation spectrum of the system as revealed by the response of the total energy as a function of the modulation frequency Omega. By using the Time Evolving Block Decimation algorithm, we are able to simulate one-dimensional systems comparable in size to those in the experiment, with harmonic trapping and across many lattice depths ranging from the Mott-insulator to the superfluid regime. Our results produce many of the features seen in the experiment, namely a broad response in the superfluid regime, and narrow discrete resonances in the Mott-insulator regime. We identify several signatures of the superfluid-Mott insulator transition that are manifested in the spectrum as it evolves from one limit to the other.